Acidic handle assemble heterogeneous carbocatalyst for facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Pandole, Satish; Suryavanshi, Amol; Kumar, Pradeep; Gajbhiye, Jayan M. (ChemistrySelect, 2019)
Acidic handle (-SO3H) assemble carbonaceous catalyst synthesized from glucose acts as a modulator for the nucleophilic fluorination reaction. The heterogeneous catalyst works with various alkyl sulfonate, halide and metal fluoride (MF), to offer a high yield of fluorinated products up to 93%. This carbonaceous catalyst is recyclable for more than five times, with no major loss of activity.
Keywords: fluorination; heterogeneous catalysis

Regioselective one-pot synthesis of 3-fluoro-imidazo[1,2-a]pyridines from styrene - Said, Madhukar S.; Mishra, Ankita; Pandole, Satish; Nayak, Rashmi A.; Kumar, Pradeep; Gajbhiye, Jayant M. (Asian Journal of Organic Chemistry, 2019)
A one-pot synthesis of C-3 fluorinated imidazopyridines (F-IMPY) is reported under the additive-free conditions from commercially available styrene and 1-fluoropyridinium tetrafluoroborate as a fluorine source. The substrate styrene undergoes keto-bromination/condensation/fluorination transformation in three sequential steps to furnish F-IMPY. This one-pot synthesis method exhibits broad substrate scope and good functional group tolerance with a good yield (up to 82%).
Keywords: fluorination; imidazopyridines (F-IMPY); One-pot synthesis

[1,3]-Claisen rearrangement via removable functional group mediated radical stabilization - Alam, Md Nirshad; Dash, Soumya Ranjan; Mukherjee, Anirban; Pandole, Satish; Marelli, Udaya Kiran; Vanka, Kumar; Maity, Pradip (Organic Letters, 2021)
A thermal O-to-C [1,3]-rearrangement of alpha-hydroxy acid derived enol ethers was achieved under mild conditions. The 2-aminothiophenol protection of carboxylic acids facilitates formation of the [1,3] precursor and its thermal rearrangement via stabilization of a radical intermediate. Experimental and theoretical evidence for dissociative radical pair formation, its captodative stability via aminothiophenol, and a unique solvent effect are presented. The aminothiophenol was deprotected from rearrangement products as well as after derivatization to useful synthons.